An Imidazolium‐Based Lipid Analogue as a Gene Transfer Agent. Issue 71 (9th November 2020) - Paulisch, Tiffany O.; Bornemann, Steffen; Herzog, Marius; Kudruk, Sergej; Roling, Lena; Linard Matos, Anna Livia; Galla, Hans‐Joachim; Gerke, Volker; Winter, Roland; Glorius, Frank
Abstract: A dicationic imidazolium salt is described and investigated towards its application for gene transfer. The polar head group and the long alkyl chains in the backbone contribute to a lipid‐like behavior, while an alkyl ammonium group provides the ability for crucial electrostatic interaction for the transfection process. Detailed biophysical studies regarding its impact on biological membrane models and the propensity of vesicle fusion are presented. Fluorescence spectroscopy, atomic force microscopy and confocal fluorescence microscopy show that the imidazolium salt leads to negligible changes in lipid packing, while displaying distinct vesicle fusion properties. Cell culture experiments reveal that mixed liposomes containing the novel imidazolium salt can serve as plasmid DNA delivery vehicles. In contrast, a structurally similar imidazolium salt without a second positive charge showed no ability to support DNA transfection into cultured cells. Thus, we introduce a novel and variable structural motif for cationic lipids, expanding the field of lipofection agents. Abstract : Can't get transfection? A transfection reagent based on a dicationic imidazolium salt was developed. Detailed analyses of membrane incorporation, adhesion of vesicles and fusogenic properties of the salt are described. Cell experiments show the successful in vitro application of this new class of transfection reagents.